Obesity Accelerates Age Defects in Mouse and Human B Cells - Frasca, Daniela; Blomberg, Bonnie B. (Frontiers in Immunology, 2020)
Obesity, similar to aging, is associated with chronic low-grade systemic inflammation, known as inflammaging, and represents a significantly higher risk for developing chronic diseases typical of old age. Immune cells are recruited to the obese adipose tissue (AT) by chemotactic molecules secreted by non-immune and immune cells in the AT, both contributing to the release of several pro-inflammatory mediators that fuel local and systemic inflammation, to the refractory response of immune cells to further in vivo and in vitro stimulation and to the induction of autoimmune B cells with potentially pathogenic repertoires. In terms of molecular mechanisms involved, leptin, an adipokine secreted primarily by adipocytes, has been proposed to be involved in the reduced generation of protective antibodies, and in the increased generation of autoimmune antibodies, further supporting the concept that obesity accelerates age defects. Leptin has also been shown to induce intrinsic B cell inflammation and B cell immunosenescence. The results presented in this review highlight the importance of weight reduction programs to improve immunity and reduce the risk for developing chronic diseases in obese and older individuals.